Analisis Faktor Yang Berhubungan Dengan Perilaku Merokok Pada Mahasiswa Di Program Studi Ilmu Keperawatan Jalur Reguler Di Fakultas Keperawatan Universitas Airlangga - Firdy Afry Liesyanto, - (2011)
Smoking behavior in nursing students are still mostly found, although they have received the lesson about smoking risk. Smoking behavior are influenced by three factors: thought and feeling factor, personal reference (social environment) factor, and resources (support facilities). The purpose of this research is to analyze factors related with smoking behavior in bachelor nursing student of Nursing Faculty Airlangga University. This research used cross sectional design. Population of this research was students enrolled in regular program from entrance year of 2007 until 2010 at Nursing Faculty of Airlangga University. Purposive sampling was used as the sampling technique. The number of students included in this research according to inclusion criteria was 19 students. Variables of tbis research are thought and feeling, social environment, support facilities and smoking bebavior. This research used Spearman's Rho as the data anlysis with level of significance (P) a:S 0.05 and degree of correlation r= 1,00. The result of this research sbowed that there was a moderate relationship between thought and feeling with the smoking behavior among nursing student (r=O,532) with level of significance p=O,O 19. There was a moderate relationship between social environment with the smoking behavior among nursing student (r=511) with level of significance p=O,026. There was a moderate relationship between supporting facility with the smoking behavior among nursing student (r=498) with level of significance p=O,030. The conclusion ofthis research is there was a relationship between thought and feeling, social environment, and supporting facility with smoking behavior among nursing student. The faculty should reform its policy system related to smoking behavior by using strict punishment for the offenders and applying nosmoking-campaign at the entire of campus. For future research, the thing that should be found out is about the therapy based on causal factors which have been studied previously in smoking behavior.